2017
DOI: 10.4048/jbc.2017.20.4.393
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of RNA Extraction from Formalin-Fixed Paraffin-Embedded Blocks for Targeted Next-Generation Sequencing

Abstract: PurposeBreast cancer has a high prevalence in Korea. To achieve personalized therapy for breast cancer, long-term follow-up specimens are needed for next-generation sequencing (NGS) and multigene analysis. Formalin-fixed paraffin-embedded (FFPE) samples are easier to store than fresh frozen (FF) samples. The objective of this study was to optimize RNA extraction from FFPE blocks for NGS.MethodsRNA quality from FF and FFPE tissues (n=5), expected RNA amount per unit area, the relationship between archiving time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Jovanovic et al . 45 demonstrated that subtyping accuracy of FFPE and FF triple negative breast cancer (TNBC) samples increased with sequencing depth, and that samples with shorter archiving time (< 4 years) were subtyped more accurately, presumably due to reduced RNA degradation which is consistent with others investigators 46 . However, Jovanovic focused their analysis on genes that did not vary between platform type, tissue processing, and RNA isolation techniques, tacitly suggesting that certain transcripts were unreliable and should be excluded.…”
Section: Discussionsupporting
confidence: 80%
“…Jovanovic et al . 45 demonstrated that subtyping accuracy of FFPE and FF triple negative breast cancer (TNBC) samples increased with sequencing depth, and that samples with shorter archiving time (< 4 years) were subtyped more accurately, presumably due to reduced RNA degradation which is consistent with others investigators 46 . However, Jovanovic focused their analysis on genes that did not vary between platform type, tissue processing, and RNA isolation techniques, tacitly suggesting that certain transcripts were unreliable and should be excluded.…”
Section: Discussionsupporting
confidence: 80%
“…Bulk RNA sequencing has successfully been performed on RNA obtained from the granuloma of nematode-infected mice using laser capture microdissection (24). However, it is now possible to isolate DNA/RNA from formalin-fixed, paraffin-embedded tissue sections (173,174). This is a great step forward, since many historical samples can now be analyzed.…”
Section: Reinterpreting Results and Use Of New Technologiesmentioning
confidence: 99%
“…While there have been other reports studying spatial heterogeneity within patient samples, these studies utilized the use of formalin fixed primary tumor tissue for the identification of genomic markers 15,16 . These studies mainly focus on identifying genomic mutations as markers of invasion as the deleterious effects of formalin on RNA integrity has been well documented and although technological advances in processing has resulted in improvements in nucleic acid quality, time of fixation plays a crucial role in the process, making such approaches inconsistent when studying gene expression 17,18 . In this study, we adopted a different approach toward understanding the heterogeneity existing within TNBC, by using a previously reported fluidic device to enrich for live cells found within the invasion front of this disease subtype for the specific purpose of studying the gene expression profile associated with invasion 19 .…”
mentioning
confidence: 99%